1954
DOI: 10.1172/jci102983
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exogenous Lipids in the Hyperlipemia and Hypercholesteremia of Nephrotic Rats 1

Abstract: The renal disease, ascites, subcutaneous edema, and hyperlipemia induced in rats by injection of rabbit anti-rat kidney serum comprise a syndrome which closely resembles the nephrotic state as it occurs in humans (1). This provides a unique opportunity to study the mechanism(s) of the disturbed lipid metabolism of the nephrotic state. In previous studies from this laboratory it was found that the hypercholesteremia of nephrotic rats cannot be ascribed either to an increased intestinal absorption of dietary cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

1955
1955
1968
1968

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…This suggests of 528 course that, with the discontinuance of the albumin infusion, the experimental rats lost their artificially maintained elevated plasma albumin levels and in so doing, again became markedly hypercholesteremic and hyperlipemic. DISCUSSION Previously it was found that the hyperlipemia and hypercholesteremia of the nephrotic rat are of endogenous origin (2) and cannot be ascribed to any increased intestinal absorption (3) or decreased intestinal excretion (5). Moreover it was shown that the hepatic synthesis of cholesterol, the major source of the plasma cholesterol (19) is not increased in the nephrotic rat (4).…”
Section: Methods and Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This suggests of 528 course that, with the discontinuance of the albumin infusion, the experimental rats lost their artificially maintained elevated plasma albumin levels and in so doing, again became markedly hypercholesteremic and hyperlipemic. DISCUSSION Previously it was found that the hyperlipemia and hypercholesteremia of the nephrotic rat are of endogenous origin (2) and cannot be ascribed to any increased intestinal absorption (3) or decreased intestinal excretion (5). Moreover it was shown that the hepatic synthesis of cholesterol, the major source of the plasma cholesterol (19) is not increased in the nephrotic rat (4).…”
Section: Methods and Resultsmentioning
confidence: 96%
“…Previous studies (1)(2)(3)(4)(5)(6)(7)(8) from this laboratory have indicated that the hypercholesteremia and hyperlipemia occurring in the experimental nephrotic syndrome induced in rats by injection of anti-rat kidney seruim are due primarily to some intravascular "trapping" phenomenion whereby the animal appears unable to remove either endogenously-produced or dietary-derived cholesterol and lipid from the plasma with its customary efficiency. However, since renal changes seemingly initiate the total nephrotic syndrome, it seems probable that this "trapping" of cholesterol and lipid which occurs in the plasma in this syndrome is related in some manner to such renal changes.…”
mentioning
confidence: 99%
“…The results of previous studies from this laboratory have indicated that the increase of lipids in the nephrotic rat is an isolated accumulation of excess lipids which is confined, at least in the early phase, to its plasma (4) and which, although capable of intensification by ingestion of dietary lipid (5), stems primarily from endogenous sources (5). Our studies also indicated that the accumulation of cholesterol in the plasma in this syndrome is not caused by any preceding change in its intestinal absorption (2) or excretion (3), or in the rate of its hepatic synthesis (6).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, in various studies concerning cholesterol and lipid metabolism in the experimental nephrotic syndrome in rats, it was found that the characteristic hypercholesteremia observed in this disorder was of endogenous origin (3) and that it did not arise from an increased rate of cholesterol synthesis or discharge into the plasma by the liver (4) nor did it arise from any intrinsic failure within the liver to convert cholesterol into cholate (4). Subsequent studies also revealed that the hypercholesteremia was not due to either an increase in the rate of intestinal absorption (5) of cholesterol nor to a decrease in the rate of intestinal excretion of cholesterol (6).…”
mentioning
confidence: 99%
“…This observed essential normality in the experimental nephrotic state of those processes concerned with the intestinal absorption and excretion of cholesterol as well as those concerned with the hepatic synthesis and conversion of cholesterol to cholate, of course, suggests that the hypercholesteremia occurring in this disorder is due to some failure in the transfer of cholesterol from the blood itself to the liver (3,7,8). If this last mechanism is responsible, then the nephrotic animal should exhibit an excess of cholesterol only in his blood and not in any other tissue or organ.…”
mentioning
confidence: 99%